2019
DOI: 10.7150/thno.34463
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA GAS5 induces abdominal aortic aneurysm formation by promoting smooth muscle apoptosis

Abstract: Objective: Long noncoding RNAs (lncRNAs) may serve as specific targets for the treatment of abdominal aortic aneurysms (AAAs). LncRNA GAS5, functionally associated with smooth muscle cell (SMC) apoptosis and proliferation, is likely involved in AAA formation, but the exact role of GAS5 in AAA is unknown. We thus explored the contribution of GAS5 to SMC-regulated AAA formation and its underlying mechanisms.Methods: Human specimens were used to verify the diverse expression of GAS5 in normal and AAA tissues. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…Apoptosis induced by GAS5 was certified by several tumor researches (Liu et al, 2018;Gao et al, 2019;He et al, 2019;Zhou et al, 2019), but in this study, we didn't detect apoptosis inducing effect of GAS5 after transfection. The cell line specificity might be the reason of this discrepancy.…”
Section: Discussionmentioning
confidence: 77%
“…Apoptosis induced by GAS5 was certified by several tumor researches (Liu et al, 2018;Gao et al, 2019;He et al, 2019;Zhou et al, 2019), but in this study, we didn't detect apoptosis inducing effect of GAS5 after transfection. The cell line specificity might be the reason of this discrepancy.…”
Section: Discussionmentioning
confidence: 77%
“…In addition to its roles as an RNA binding protein, YBX1 also functions as a transcription factor 58 . Previous studies showed lncRNA can bind to YBX1 and influence the transcriptional activities of YBX1 59 .…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies have demonstrated the direct role of lncRNAs in the pathogenesis of various human diseases including tumors, inflammatory, cardiovascular, and immunological diseases [ 3 , 5 ]. In many studies, the regulatory mechanism of lncRNAs in aortic aneurysms was also shown, which was directly associated with the formation, growth and dissection of the aorta ( Table 1 ) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In recent years, increasing studies have focused on role lncRNAs in the pathogenesis of IAs.…”
Section: Lncrnas and Iasmentioning
confidence: 99%